Potential anti-diabetic activity of Bombax ceiba (Bangladesh Journal of Pharmacology, 2013)
Bombax ceiba bark extract was evaluated for its hypoglycemic and hypolipide-mic potential through normal and streptozotocin-induced diabetic rats administered with graded oral doses (200, 400, 600 mg/kg/day) for 21 days. The results showed that a dose of 600 mg/kg of B. ceiba extract is the most effective to cause significant (p